2021
DOI: 10.1080/2314808x.2021.1905464
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biofilm dependent catheter associated urinary tract infections: Characterization, antibiotic resistance pattern and risk factors

Abstract: Biofilms cause recurrent and resistant device-related infections. We aimed to detect the prevalence of biofilm-dependent catheter-associated urinary tract infections (CAUTI) among catheterized patients, identify bacterial pathogens, antibiotic resistance pattern and risk factors associated with biofilm production. Adult and pediatric patients admitted to Mansoura University Urology and Nephrology Center and fulfilling the criteria of CAUTI were enrolled in this study. urine sample and a part of urinary cathete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
(45 reference statements)
1
11
0
1
Order By: Relevance
“…Regarding resistance to the biofilm isolates, this study is true for other studies that showed higher resistance among the biofilm isolates than the non-biofilm isolates [7] [21] [30]. High resistance to Ciprofloxacin was observed in similar studies which agree with this study revealing trimethoprim and ciprofloxacin as higher resistance to biofilm pathogens [21].…”
Section: Antibiotic Resistance Of Urine and Biofilm Isolatessupporting
confidence: 87%
See 2 more Smart Citations
“…Regarding resistance to the biofilm isolates, this study is true for other studies that showed higher resistance among the biofilm isolates than the non-biofilm isolates [7] [21] [30]. High resistance to Ciprofloxacin was observed in similar studies which agree with this study revealing trimethoprim and ciprofloxacin as higher resistance to biofilm pathogens [21].…”
Section: Antibiotic Resistance Of Urine and Biofilm Isolatessupporting
confidence: 87%
“…Nitrofurantoin had lower resistance rates and can be considered for CAUTI treatment contrary to similar studies elsewhere [7] [31]. Generally, in concordant with Qayoom, K. pneumoniae isolated from biofilm exhibited higher resistance levels than the other isolates [32] and these could be attributed to K. pneumoniae's high potential to producing biofilm [7].…”
Section: Antibiotic Resistance Of Urine and Biofilm Isolatesmentioning
confidence: 64%
See 1 more Smart Citation
“…Moreover, the prevalence of biofilm-dependent CAUTIs was about 82 %. The majority (81.25 %) of patients with catheters inserted for ≤14 days suffered from mono-bacterial colonization inside the catheter, and 42.11 % of patients with catheters inserted for one month had poly-microbial colonization (Ramadan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Between 50% and 60% of adult women have faced at least one UTI in their life, and close to 10% of postmenopausal women suggest that they had a UTI in the previous year (Alos, 2005). A biofilm can be defined as microorganisms bound to a surface of each other with the existence of an extracellular matrix made of secreted elements of the organisms and/or of components of the microorganisms themselves and it causes frequent and resistant device-related infections (Ramadan et al, 2021). Biofilms provide an environment for poor antibiotic penetration and horizontal transfer of virulence genes which favors the progression of Multidrug-resistant organisms (MDRO) (Katongole, 2020).…”
Section: Introductionmentioning
confidence: 99%